Monitoring linear accelerators electron beam energy constancy with a 2D ionization chamber array and double‐wedge phantom. Issue 1 (21st October 2019) - Gao, Song; Chetvertkov, Mikhail A.; Simon, William E.; Sadeghi, Amir; Balter, Peter A.
Abstract: Validate that a two‐dimensional (2D) ionization chamber array (ICA) combined with a double‐wedge plate (DWP) can track changes in electron beam energy well within 2.0 mms as recommended by TG‐142 for monthly quality assurance (QA). Electron beam profiles of 4–22 MeV were measured for a 25 × 25 cm 2 cone using an ICA with a DWP placed on top of it along one diagonal axis. The relationship between the full width half maximum (FWHM) field size created by DWP energy degradation across the field and the depth of 50% dose in water (R50 ) is calibrated for a given ICA/DWP combination in beams of know energies (R50 values). Once this relationship is established, the ICA/DWP system will report the R50 FWHM directly. We calibrated the ICA/DWP on a linear accelerator with energies of 6, 9, 12, 16, 20, and 22 MeV. The R50 FWHM values of these beams and eight other beams with different R50 values were measured and compared with the R50 measured in water, that is, R50 Water. Resolving changes of R50 up to 0.2 cm with ICA/DWP was tested by adding solid‐water to shift the energy and was verified with R50 Water measurements. To check the long‐term reproducibility of ICA/DWP we measured R50 FWHM on a monthly basis for a period of 3 yr. We proposed a universal calibration procedure considering the off‐axis corrections and compared calibrations and measurements on three types of linacs (Varian TrueBeam, Varian C‐series, and Elekta) with different nominal energies and R50 values. For all 38 beams on same type of linac with R50 values over a range of 2–8.8 cm, the R50 FWHM reported by the ICA/DWP system agreed with that measured in water within 0.01 ± 0.03 cm (mean ± 1σ) and maximum discrepancy of 0.07 cm. Long‐term reproducibility results show the ICA/DWP system to be within 0.04 cm of their baseline over 3 yr. With the universal calibration the maximum discrepancy between R50 FWHM and R50 Water for different types of linac reduced from 0.25 to 0.06 cm. Comparison of R50 FWHM values and R50 Water values and long‐term reproducibility of R50 FWHM values indicates that the ICA/DWP can be used for monitoring of electron beam energy constancy well within TG‐142 recommended tolerance.